Calculations and Analysis of n+93Nb Reaction. (3rd August 2017) - Liang, Haiying; Wu, Zhendong; Zhang, Zhengjun; Han, Yinlu; Jiao, Xuesheng
Abstract: All cross sections, angular distributions, energy spectra, and double differential cross sections are consistently calculated and analyzed for n+ 93 Nb reaction at incident neutron energy up to 200 MeV based on the nuclear theoretical models. The theoretical calculated results are compared with the existing experimental data and the evaluated data in ENDF/B-VII, JENDL-4, and TENDL-2015. The calculated results agree with the experiential data.